Modeling ultra-high frequency radiation emission in PIC codes - Pardal, M. (2018)
From the mysterious?ray bursts, which can be studied through the spatiotemporal structure of the radiation we receive, to the creation of sources of x-rays capable of probing nanoscale structures, radiation emission by relativistic charges is a key research field in plasma physics.The processes behind radiation emission in plasmas result from strongly non-linear many body interactions which involve relativistic effects, so they are best modeled through Particle-In-Cell (PIC) simulations. However, capturing this radiation directly in PIC simulations is very challenging due to the large disparity between the temporal and spatial scales associated with such phenomena. Current algorithms only describe radiation processes in the Fourier space (e.g.JRAD [1]), missing the spatiotemporal features of the emitted radiation, which is crucial to many fields, such as super-resolution microscopy [2] and astrophysics [3].